Evaluation of the implementation of good manufacturing practices (gmp) in cv panda food, a special region of yogyakarta - Saputra, Agum Dwi; Rahayu, Wahidah Mahanani (Journal of Halal Science and Research, 2022)
CV Panda Food is a company engaged in the snack food industry in the form of nori (seaweed) which Mr. Stenly Hendi Avanda founded in 2012. There are several products and various flavors offered by CV Panda Food, such as Mininori Seasoned Chicken and Roast Beef, Panda Seaweed Original Flavor, Spicy Flavor, and Barbeque Flavor. To keep the food free of potential biological, chemical, and other pollutants that could harm, interfere with, or otherwise put human health in jeopardy so that it is safe to consume, CV Panda Food needs to be evaluated on Good Manufacturing Practices (GMP). Mininori production, which refers to the Regulation of the Minister of Industry of the Republic of Indonesia Number 75/M-IND/PER/2010, consists of location, buildings, facilities and sanitation, machinery and equipment, materials, process control, final products, laboratories, workers, packaging, labels and product description, storage, maintenance and sanitation programs, transportation, documentation and recording, training, product recall and program implementation. The purpose of implementing the Practical Work is to implement GMP at CV Panda Food concerning the Regulation of the Minister of Industry of the Republic of Indonesia No. 75/M-IND/PER/7/2010 and the obstacles found in CV Panda Food in implementing GMP in Miniori production. The methods used in data collection are observation, interviews, direct practice, documentation, and literature study. The results are that CV Panda Food has not fully implemented the GMP Regulation of the Minister of Industry of the Republic of Indonesia No. 75/M-IND/PER/7/2010. There are 83.07% appropriate, and 16.93% non-conformance from 18 aspects due to human factors, materials, environment, and methods, namely doors, ventilation, and windows not equipped with screens, not having a laboratory, walls, and floors form elbows so that the production environment is challenging to clean, there is no pest prevention, lack of dryers or tissue and lack of firm action on GMP violators, lack of awareness in the implementation of sanitation, and there is still garbage that accumulates in the production room due to lack of monitoring from the head production that pollutes the environment.